STRATEGIC SPEECH: A FUNCTIONAL LINGUISTIC ANALYSIS OF CORPORATE STRATEGY DISCOURSE - Asfah, Indrawaty; Lely Novia; Nurwahida (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2025)
This paper explores how linguistic choices in corporate strategy discourse reflect strategic goals—informing, persuading, and engaging—through the lens of Halliday’s Systemic Functional Linguistics and Jakobson’s Communication Model. Using data from the video “The Great Debate on Corporate Strategy”, the study analyzes how expert speakers deploy ideational, interpersonal, and textual functions (Halliday) alongside referential, conative, emotive, and poetic functions (Jakobson). The findings reveal that corporate discourse is multifunctional, blending technical precision, rhetorical appeal, and stylistic engagement to achieve communicative impact. The paper concludes that integrating both linguistic frameworks offers a comprehensive understanding of strategic speech in professional contexts.